Design and construction of a tesla coil 1680 W, as a tool for teaching basic concepts in electric power systems - Castro Galeano, Juan Carlos; Pinto Salamanca, Maria Luisa; Amaya Quitián, Maira Fernanda (Universidad Pedagógica y Tecnológica de Colombia, 2014)
Tesla coil is a type of resonant transformer, which operates at high frequencies and raises the voltage, it’s built with two coils electrically coupled into an air core which produces observable effects by the human eye as sparks and electrical discharges. This article presents the design and construction of a 1680 W Tesla coil with a rupture distance of one meter length. The coil could be used as a teaching learning tool in the teaching of the fundamental concepts of electrical power systems as: corona effect, resonance RLC circuits, electric and magnetic fields, energy transmission without conductors and high voltage.